Analisis Faktor – Faktor Yang Mempengaruhi Keputusan Pembelian Dalam Memilih Menu Minuman (Studi Kasus Pada Konsumen Asmaraloka Coffee Malang) - Agus Sa’dan Al Irfani; Agus Widarko; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract Based on research conducted with the aim of knowing the simultaneous effect of price, product, promotion, and location on purchasing decisions in choosing a case study drink menu at the coffee shop asmaraloka coffee. This research is an associative research type with a quantitative approach. The method used is multiple linear regression. The sampling technique used the formula from Malhotra with the calculation results of 85 samples. The sampling technique used in this research is purposive sampling where every customer in the population has the opportunity to be a sample. To solve the problem in this study using SPSS assistance with validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, f test, and t test. From this study, it was found that the price, product, promotion, and location variables had a simultaneous effect on purchasing decisions, partially the price and product variables had an effect on purchasing decisions, but tepromotion and location variables had no effect on purchasing decisions. Meanwhile, the variables of price, product, promotion and location simultaneously influence purchasing decisions. Keywords: Price, Product, Promotion, Location, Purchase Decision